2005
DOI: 10.1192/apt.11.6.440
|View full text |Cite
|
Sign up to set email alerts
|

Potentially hazardous drug interactions with psychotropics

Abstract: Of the many interactions with psychotropic drugs, a minority are potentially hazardous. Most interactions are pharmacodynamic, resulting from augmented or antagonistic actions at a receptor or from different mechanisms in the same tissue. Most important pharmacokinetic interactions are due to effects on metabolism or renal excretion. The major enzymes involved in metabolism belong to the cytochrome P450 (CYP) system. Genetic variation in the CYP system produces people who are 'poor', 'extensive' or 'ultra-rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 12 publications
0
33
1
1
Order By: Relevance
“…The potential for DDIs involving lysosomes is a topic of speculation (Daniel and Wojcikowski, 1999;Chadwick et al, 2005;Funk and Krise, 2012;Logan et al, 2012). Although coadministration-related subtle changes in organ distribution may occur, there are no known clinical examples of lysosomal-related DDI in which changes in drug (1) the substrate and inhibitor were added simultaneously (coincubation), (2) the inhibitor was added 5 minutes before substrate but was not removed (preincubation and coincubation), and (3) the inhibitor was added 5 minutes before the substrate, but the cells were washed before adding the substrate (preincubation), as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for DDIs involving lysosomes is a topic of speculation (Daniel and Wojcikowski, 1999;Chadwick et al, 2005;Funk and Krise, 2012;Logan et al, 2012). Although coadministration-related subtle changes in organ distribution may occur, there are no known clinical examples of lysosomal-related DDI in which changes in drug (1) the substrate and inhibitor were added simultaneously (coincubation), (2) the inhibitor was added 5 minutes before substrate but was not removed (preincubation and coincubation), and (3) the inhibitor was added 5 minutes before the substrate, but the cells were washed before adding the substrate (preincubation), as described in Materials and Methods.…”
Section: Discussionmentioning
confidence: 99%
“…Competition for lysosomal trapping has been the subject of some speculation as a potential mechanism of drug-drug interactions (DDIs) (Daniel and Wojcikowski, 1999;Chadwick et al, 2005;Funk and Krise, 2012;Logan et al, 2012). Because many central nervous system and cardiovascular drugs are lysosomotropics (drugs that undergo lysosomal sequestration), there is the possibility that concomitant administration of lysosomotropics could lead to elevated drug exposure levels as competition for lysosomal sequestration increases or lysosomal pH is elevated by amine accumulation Vestal et al, 1980;Logan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study, half of all older Australians admitted to hospital for hip fracture used at least two medicines associated with falls or hip fracture during the 6 weeks before hospital admission [2]. The concurrent use of multiple psychoactive medicines could increase a patient’s risk owing to the potential for pharmacodynamic or pharmacokinetic interactions between the medicines [3]. For example, an antidepressant can add to the sedative effect of a benzodiazepine [4].…”
Section: Introductionmentioning
confidence: 99%
“…73 CYP2D6 Table 8 presents examples of drugs that inhibit CYP450 enzymes. 34 It must be emphasized that CYP activity can be inhibited by many drugs at clinically relevant concentrations, and data about potential drug-drug interactions and concentration-dependent adverse drug reactions must be available to physicians. Important examples are cimetidine, which inhibits several different CYPs, and the HIV-protease inhibitors that inhibit CYP3A4.…”
Section: Tpmt Polymorphismsmentioning
confidence: 99%
“…32 Like CYP enzymes, P-glycoprotein can be induced and inhibited by other drugs, which creates the potential for drug interactions (Table 4). 33,34 The study of 247 individuals enabled identification of 110 different MDR1 haplotypes. 35 In predicting MDR1 phenotype, results of digoxin pharmacokinetic studies evaluated on the basis of steady-state drug plasma concentration have shown that haplotype analysis was more accurate than single nucleotide polymorphism (SNP) estimation.…”
Section: P-glycoprotein: Protein Drug Transportermentioning
confidence: 99%